Old vs new: Risk factors predicting early onset colorectal cancer - Syed, Aslam R (World J Gastrointest Oncol, 2019)
BACKGROUND: Colorectal cancer (CRC) is the second leading cause of all cancer related deaths in the United States and Europe. Although the incidence has been decreasing for individuals’ ≥ 50, it has been on the rise for individuals < 50. AIM: To identify potential risk factors for early-onset CRC. METHODS: A population-based cohort analysis using a national database, Explorys, screened all patients with an active electronic medical record from January 2012 to December 2016 with a diagnosis of CRC. Subgroups were stratified based on age (25 – 49 years vs ≥ 50 years). Demographics, comorbidities, and symptom profiles were recorded and compared between both age groups. Furthermore, the younger group was also compared with a control group consisting of individuals aged 25-49 years within the same timeframe without a diagnosis of CRC. Twenty-data points for CRC related factors were analyzed to identify potential risk factors specific to early-onset CRC. RESULTS: A total of 68860 patients were identified with CRC, of which 5710 (8.3%) were younger than 50 years old, with 4140 (73%) between 40-49 years of age. Multivariable analysis was reported using odds ratio (OR) with 95%CI and demonstrated that several factors were associated with an increased risk of CRC in the early-onset group versus the later-onset group. These factors included: African-American race (OR 1.18, 95%CI: 1.09-1.27, P < 0.001), presenting symptoms of abdominal pain (OR 1.82, 95%CI: 1.72-1.92, P <0.001), rectal pain (OR 1.50, 95%CI: 1.28-1.77, P < 0.001), altered bowel function (OR 1.12, 95%CI: 1.05-1.19, P = 0.0005), having a family history of any cancer (OR 1.78, 95%CI: 1.67-1.90, P < 0.001), gastrointestinal (GI) malignancy (OR 2.36, 95%CI: 2.18-2.55, P < 0.001), polyps (OR 1.41, 95%CI: 1.08-1.20, P < 0.001), and obesity (OR 1.14, 95%CI: 1.08-1.20, P < 0.001). Comparing the early-onset cohort versus the control group, factors that were associated with an increased risk of CRC were: male gender (OR 1.34, 95%CI: 1.27-1.41), P < 0.001), Caucasian (OR 1.48, 95%CI: 1.40-1.57, P < 0.001) and African-American race (OR 1.25, 95%CI: 1.17-1.35, P < 0.001), presenting symptoms of abdominal pain (OR 4.73, 95%CI: 4.49-4.98, P < 0.001), rectal pain (OR 7.48, 95%CI: 6.42-8.72, P < 0.001), altered bowel function (OR 5.51, 95%CI: 5.19-5.85, P < 0.001), rectal bleeding (OR 9.83, 95%CI: 9.12-10.6, P < 0.001), weight loss (OR 7.43, 95%CI: 6.77-8.15, P < 0.001), having a family history of cancer (OR 11.66, 95%CI: 10.97-12.39, P < 0.001), GI malignancy (OR 28.67, 95%CI: 26.64-30.86, P < 0.001), polyps (OR 8.15, 95%CI: 6.31-10.52, P < 0.001), tobacco use (OR 2.46, 95%CI: 2.33-2.59, P < 0.001), alcohol use (OR 1.71, 95%CI: 1.62-1.80, P < 0.001), presence of colitis (OR 4.10, 95%CI: 3.79-4.43, P < 0.001), and obesity (OR 2.88, 95%CI: 2.74-3.04, P < 0.001). CONCLUSION: Pending further investigation, these potential risk factors should lower the threshold of suspicion for early CRC and potentially be used to optimize guidelines for early screening.